Evaluating the Effectiveness of a Local Food-Based Supplemental Feeding Program in Addressing Chronic Energy Deficiency Among Pregnant Women in Temanggung District - Herlina, Beti (BKM Public Health and Community Medicine, 2024)
Background: Chronic Energy Deficiency (CED) in pregnant women is a significant health issue that affects the prevalence of stunting in children. In response, Temanggung District has implemented a Supplemental Feeding Program (SFP) using local food sources to improve the nutritional status of pregnant women and reduce the risk of stunting in children. Objective: This study aims to evaluate the effectiveness and challenges of the Supplemental Feeding Program (SFP) in addressing Chronic Energy Deficiency (CED) among pregnant women in Temanggung District, focusing on the suitability of local food materials and the program's impact on reducing the prevalence of CED. Method: A qualitative descriptive approach was used to assess the implementation of the Supplemental Feeding Program (SFP). Data were collected through in-depth interviews and observations involving health workers, program beneficiaries, and policymakers, utilizing purposive sampling to ensure a comprehensive understanding of the program's implementation and outcomes. Results: The Supplemental Feeding Program (SFP) successfully reached nearly all the targeted pregnant women with Chronic Energy Deficiency (CED) in Temanggung District. However, challenges remain, including issues related to the availability and distribution of quality food materials, limitations in trained human resources, and socio-cultural barriers that affect the acceptance and integration of dietary practices within the community. Conclusion: Recommendations include enhancing inter-agency coordination, refining community education strategies to address negative cultural perceptions towards certain foods, and increasing resource allocation to improve the availability and distribution of food materials. These improvements are expected to enhance the program's effectiveness in reducing the prevalence of Chronic Energy Deficiency (CED) and stunting.